Peningkatan hasil belajar siswa melalui pendekatan Open-Ended pada pembelajaran ukuran pemusatan data - Suismanto Suismanto (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
This class action study was carried out with the intention of optimizing the learning outcomes of class XII TKJ A students using an open-ended learning model. Application of teaching using an open-ended learning model was carried out from 3 September 2020 to 12 October 2020 in class XII TKJ A SMK N 1 Pleret which was attended by 30 students. This data collection was carried out through observation and tests carried out in 2 cycles with each cycle consisting of four levels that had to be carried out, namely planning, action, observation and reflection. The implementation was carried out online because in conditions during the Covid – 19 era. Meanwhile, the data assessment was in the form of descriptive, quantitative and qualitative data. For the assessment of the results of the study of research teachers (collaborators) in cycle I was 62.49% and in cycle II there was an increase to 85.83%. For the results of the assessment of the attitude aspect in the first cycle of 62.49% to 85.83% in the second cycle with students entering the very active level. For the research results of the cognitive aspects in the pre-cycle period, the average value was only 70.33%, there was an increase to 87.50% and the acquisition of classical learning outcomes had exceeded the provisions of the success indicator, the average value was 75%, seeing this fact, it can be concluded that The open-ended learning model can increase the learning outcomes of Mathematics in class XII TKJ A SMK N 1 Pleret.